Book review: Pierre Bourdieu, Classification Struggles: General Sociology, Volume I. Lectures at the College de France, 1981–82. (April 2020) - Kumar, Ratheesh
Pierre Bourdieu, Classification Struggles: General Sociology, Volume I. Lectures at the College de France, 1981–82 . Cambridge: Polity Press, 2018, 182 pp. (hardback). ISBN: 978-1-5095-13277.